Pathogenic fungi found in wheat seeds and medium early maturity, produced in three parts of Rio Grande do Sul, Brazil - Durante Danelli, Anderson (2012)
Seed samples of wheat harvest in 2010 from Santo Augusto, Passo Fundo and Vacaria, RS; were plated on gerbox acrylic sterilized culture medium PSA (potato, sucrose and agar) plus antibiotics. Were used 400 seeds of each cultivar total of 45 cultivars. Were distributed equally spaced 25 seeds in each seedling with four replications, totaling 100 seeds per replicate. The seeds were incubated at 25 ± 2°C in an incubator with a photoperiod of 12 hours for 12 days. The experimental design was blocks and the experimental unit consists of four gerbox containing 25 seeds each. Was considered to be infected the seed of conidiophore presence and/or conidia of the fungus. The data were transformed to (x+1)1/2 and subjected to analysis of variance and means compared by Tukey test at 5% probability. Fungi F. graminearum and Alternaria spp. were detected in high incidence in most lots, performing at respectively 96.0% and 98.0% of samples, thereafter Bipolaris spp. So too, Drechslera siccans was found in 41.5% of samples showing that their incidence is increasing.